2022
DOI: 10.1371/journal.pone.0274829
|View full text |Cite
|
Sign up to set email alerts
|

Construction and evaluation of a self-replicative RNA vaccine against SARS-CoV-2 using yellow fever virus replicon

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a global threat. To forestall the pandemic, developing safe and effective vaccines is necessary. Because of the rapid production and little effect on the host genome, mRNA vaccines are attractive, but they have a relatively low immune response after a single dose. Replicon RNA (repRNA) is a promising vaccine platform for safety and efficacy. RepRNA vaccine encodes not only antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The same result was found by Nakamura et al (2022), with mRNA that functions like saRNA having higher copy numbers than normal mRNA sampled from transfected BHK21 cells. Their saRNA's copy numbers decreased at 72 hours post-transfection.…”
Section: Mrna Quantification Of Mice Samplessupporting
confidence: 79%
See 1 more Smart Citation
“…The same result was found by Nakamura et al (2022), with mRNA that functions like saRNA having higher copy numbers than normal mRNA sampled from transfected BHK21 cells. Their saRNA's copy numbers decreased at 72 hours post-transfection.…”
Section: Mrna Quantification Of Mice Samplessupporting
confidence: 79%
“…Their results show that the highest mRNA concentration was found in injection location muscle and lymph nodes, while most mRNA concentration has reduced starting from eight days post-injection to 60 days post-injection except on lymph node. All of these results showed reduction in mRNA concentration starting from three days on this research (Table 1) and research by Nakamura et al (2022) and eight days post-injection found in Maruggi et al (2022) post-injection, but there might be mRNA left in the mice lymph node. For future research, further analysis in pCDNA3.1-SRM RNA polymerase function duration and capability are necessary.…”
Section: Mrna Quantification Of Mice Samplessupporting
confidence: 76%
“…Compared to conventional mRNA, repRNA triggers prolonged gene expression lasting weeks to months after a single injection, making it a promising candidate for sustained antigen expression in vaccine design [8]. repRNA vaccines have emerged as promising candidates, showcasing exemplary safety and immunogenicity, and have already demonstrated encouraging results in various clinical trials [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In a second part, we describe the design and performance of currently licensed recombinant vaccines and vaccine candidates that are based on YF17D as a live viral vector. The use of subgenomic YF17D replicons [19,20] as a basis for self-amplifying RNA vaccines [21] or of related Flaviviruses as live viral vectors [22][23][24][25][26] is not considered. Technical aspects of recombinant vaccine virus construction, vaccine safety and unique requirements of preclinical animal testing linked to the biology of YF17D are described in separate text boxes.…”
mentioning
confidence: 99%